Развитие теории мгновенной мощности трехфазной сети в условиях сетецентризма - Сокол, Е.И; Сиротин, Ю.А.; Иерусалимова, Т.С.; Гриб, О.Г.; Швец, С.В.; Гапон, Д.А (Електротехніка і електромеханіка, 2017)
Обеспечение сетецентрического подхода к режиму управления трехфазной сетью и оценка сбалансированности режима сети с учетом влияния мгновенной мощности на величину потерь даст возможность исключить появление
нулевой последовательности и, тем самым, повысить качество электроэнергии Забезпечення мережецентричного підходу до режиму управління трифазною мережею і оцінка збалансованості режиму мережі з урахуванням впливу миттєвої потужності на величину втрат дасть можливість виключити появу
нульової послідовності і, тим самим, підвищити якість електроенергії. Purpose. Information technologies allow multidimensional analysis of information about the state of the power system in a single
information space in terms of providing network-centric approach
to control and use of unmanned aerial vehicles as tools for condition monitoring of three-phase network. Methodology. The idea of
energy processes in three independent (rather than four dependent) curves vector-functions with values in the arithmetic threedimensional space adequately for both 4-wire and 3–wire circuits.
The presence of zero sequence current structural (and mathematically) features a 4-wire scheme of energy from a 3-wire circuit.
The zero sequence voltage caused by the displacement of the zero
voltage phases. Offset zero in the calculations can be taken into
account by appropriate selection of the reference voltages. Both of
these energetic phenomena with common methodical positions are
described in the framework of the general mathematical model, in
which a significant role is played by the ort zero sequence. Results. Vector approach with a unified voice allows us to obtain
and analyze new energy characteristics for 4–wire and 3–wire
circuits in sinusoidal and non-sinusoidal mode, both in temporal
and frequency domain. Originality. Symmetric sinusoidal mode is
balanced, even with non-zero reactive power. The converse is not
true. The mode can be balanced and unbalanced load. The mode
can be balanced and unbalanced voltage. Practical value. Assessing balance in network mode and the impact of instantaneous
power on the magnitude of the losses, will allow to avoid the
appearance of zero sequence and, thus, to improve the quality of
electricity